Improving for Speaking Skills Using Siniar-Based Learning Media to Form Personal Branding of PGSD Students at West Sulawesi University - St Harpiani; Muh. Inayah A.M; Putri Indriani; Agung Agung (Universitas Muhammadiyah Enrekang, 2024)
Speaking skills are one of the components of language skills that play a very prominent role in enhancing a person's communication skills. The rapid advancement of technology has a major consequence on the use of IT-based learning media, including in improving speaking skills. The purpose of this study was to describe the improvement of speaking skills using podcast-based learning media to form the personal branding of Primary Teacher Education students at the Universitas Sulawesi Barat and to develop students' public speaking skills. Therefore they could acknowledge their potential and begun to form personal branding with an acceptable image. The method used was a mixed method. The selection of research targets used the convenience sampling method involving 28 students of the Primary Teacher Education Study Program, batches of 2022 and 2023. The results obtained were an increase in students' speaking skills using podcast-based learning media. Meanwhile, student responses revealed that podcast media was very helpful in enhancing speaking skills because it instructed oneself to communicate well, and could eliminate nervousness. Mastery of speaking skills can be an alternative to forming personal branding. This is because someone can form their characteristics through speaking style.